Digital economy's transformative impact on regional growth: evidence from ASEAN countries - Zhenyi, Mawang; Lai, Wei Sieng (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the impact of digital economy development on regional economic growth. It further determines the role of digital economy in enhancing industrial structures in regional economic growth. Using panel data from ASEAN countries spanning 2011-2019, this study employs the entropy weight method to establish an index system to evaluate the development of digital economy among ASEAN countries. It additionally employs fixed effect model to investigate the relationship between digital economy development and economic growth. Furthermore, a mediation effect model is employed to analyse the indirect effects of digital economy through the advancement of industrial structure in promoting economic growth. This study found that the development of the digital economy contributes to the economic growth of ASEAN countries. It also highlights the digital economy's role in enhancing industrial structures as a mediating factor in this growth, noting a nonlinear relationship where the impact on regional economic growth increases progressively. Simultaneously, this study finds that the development of the digital economy exhibits regional heterogeneity in ASEAN countries, with varying levels of development based on income. This study enriches the evaluation methods and research framework of digital economy research in ASEAN. The entropy weight method is introduced as an evaluation index system for digital economy development in ASEAN countries. Utilizing a two-way fixed effects model and mediation effects model, this study explores the promoting effect of digital economy development on economic growth, revealing the indirect effect of digital economy in promoting industrial structure and economic growth. The findings suggest that ASEAN countries stand to benefit immensely from the burgeoning digital economy, which promises to inject new vitality into regional economic expansion. The study underscores the importance of fostering digital economy advancements to achieve sustained economic development and structural transformation.